Customer acceptance of cashless payment systems among UiTM Kampus Bandaraya Melaka Staffs / Mohd Faez Zainal Abidin - Zainal Abidin, Mohd Faez (Faculty of Business and Management, 2019)
The purpose of this study is to identify the factors influencing customer acceptance of cashless payment systems among UiTM Kampus Bandaraya Melaka staffs from both non-academic and academic departments. The sample of this study is 102 respondents. The questionnaire has been distributed based on the number selected in the list name of the staffs. This study has been conducted by the researcher to determine the sample, the reliability and validity of the questionnaire and identify the significance of the variables. The researcher collected the data from primary data, secondary sources and data analysis technique by using SPSS version 20. There are three variables that involve in this study which are perceived usefulness, perceived ease of use and perceived risk. The result sated that all three variables are significant and had positive relationship with customer acceptance of cashless payment systems. From these three variables, perceived usefulness is the most influential factor influencing customer acceptance of cashless payment systems among UiTM Kampus Bandaraya Melaka staffs.